HUBUNGAN PENGETAHUAN DAN DUKUNGAN SUAMI TERHADAP KEPATUHAN KB SUNTIK ULANG DI PMB - Septia, Qori Armiza; Yulita, Emi; Aldinda, Tharra Widadari; Hayati, Iznirrahma; Aulia, Eci (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: The trend pattern of contraceptive use in Indonesia shows that injectable contraceptive methods have been very popular in recent times, the reason is because injectable contraception is more practical and simple (Qomariah & Sartika, 2019). However, the most frequent problem in using injectable contraceptives is that birth control acceptors are late in getting the injection. Based on the results of the preliminary survey, the reason for the delay in the return visit was because the mother said she lacked knowledge and did not get her husband's support, this affected compliance. This study aims to determine the relationship between husband's knowledge and support on contraceptive compliance with repeated injections in the Independent Practice of Midwives Asnamisdarwita, Pekanbaru City. This research uses an analytical survey method with a cross-sectional approach, the data collection method is carried out by distributing questionnaires. The results of the research show that there is a significant value of knowledge regarding compliance with contraceptive re-injections in the Independent Practice of Midwives Asnamisdarwita, Pekanbaru City, obtained a value (p-value = 0.012) and husband's support for compliance with contraceptive re-injections in the Independent Practice of Midwives Asnamisdarwita, Pekanbaru City, obtained a value (p -value = 0.047)<0.05 so it can be concluded that there is a relationship between knowledge and husband's support for compliance with re-injection contraception in the Independent Practice of Midwives Asnamisdarwita in Pekanbaru City. With this, it is hoped that midwives can provide counseling to new and repeat family planning acceptors about the importance of re-injecting according to schedule so that injectable family planning is effective.Keywords: Knowledge, Husband's Support, Compliance with Repeat Injectable Family Planning